DAMPAK CORPORATE GOVERNANCE TERHADAP KEPUTUSAN DIVIDEN (Literature Review Pada Negara-negara di Asia, Australia dan Afrika) - Nur Hidayati; Hadi Sunaryo (University of Merdeka Malang, 2016)
AbstractThis study aimed to analyze the impact of corporate governance towards dividend policy in several countriesn Asia, Australia, and Africa. Focusing on literature review and analyzing the result with theoretical andpractical implication disscussed in this paper. Based on paper review, we generalize corporate governancehave significant and negative effect towards dividend policy. But we realize that result from such countriestudied show neither confirmation or rejection to subtitutive theory. There are also conceptual model proposedrom literature review from previous empirical result about effect of corporate governance toward dividend policy.Suggest for future research discussed to gain valuable information about corporate governance anddividend policy.